Analytic hierarchy process on criteria selection on the ideal partner among university students - Mohamad Aris, Nur Syazwani Aqilah; Che Him, Norziha; Rusiman, Mohd Saifullah; Shafi, Muhammad Ammar (2021)
. This study investigates the criteria of an ideal partner among university student by using Analytic Hierarchy Process (AHP) in Universiti Tun Hussein Onn Malaysia (UTHM). A questionnaire survey has been distributed to respondents in nine faculties in UTHM with the total of 11 criteria of an ideal woman and 11 criteria of an ideal man have been listed for respondents to rank based on their priorities. The objective of the study is to determine the priority criteria of man and woman that most students considered before getting marriage. Some comparison of selection criteria for an ideal partner between Malay and non-Malay has been analysed. Result shows the main priority criteria for an ideal man are religious followed by responsible, loyal, honest, loving, mature, hygiene, ambitious, rich, intelligent and good looking. Meanwhile, the main priority criteria for an ideal woman are religious followed by honest, motherly, patient, beautiful, polite, cooking, friendly, cheerful, intelligent and independent. The comparison between non-Malay present the main criteria of an ideal man and ideal woman are responsible and beautiful. One of the significant findings throughout the research was majority of the respondents agreed that religious become the main criteria in selecting a right partner and highly significant difference in selection criteria of an ideal partner between Malay and non-Malay.